Overexpression of Mitochondrial Ligases Reverses Rotenone-Induced Effects in a Drosophila Model of Parkinson’s Disease - Doktór, Bartosz; Damulewicz, Milena; Pyza, Elzbieta (Frontiers in Neuroscience, 2019)
Mul1 and Park are two major mitochondrial ligases responsible for mitophagy. Damaged mitochondria that cannot be removed are a source of increased level of free radicals, which in turn can destructively affect other cell organelles as well as entire cells. One of the toxins that damages mitochondria is rotenone, a neurotoxin that after exposure gives symptoms typical of Parkinson's disease. In the present study, we showed that overexpressing genes encoding mitochondrial ligases protects neurons during treatment with rotenone. Drosophila strains with overexpressed mul1 or park show significantly reduced degeneration of dopaminergic neurons, as well as normal motor activity during exposure to rotenone. In the nervous system, rotenone affected synaptic proteins, including Synapsin, Synaptotagmin and Disc Large1, as well as the structure of synaptic vesicles, while high levels of Mul1 or Park suppressed degenerative events at synapses. We conclude that increased levels of mitochondrial ligases are neuroprotective and could be considered in developing new therapies for Parkinson's disease.